REDESAIN PASAR CIBARUSAH DENGAN PENDEKATAN ARSITEKTUR PERILAKU - Sari, Pawitra; Sari, Putri Anggun; Wawan Hermansyah (Universitas Pelita Bangsa, 2021)
Cibarusah Market is a traditional market located at Jalan Raya Cibarusah No. 41, Cibarusah Kota Village, Cibarusah District, Bekasi Regency, West Java Province. Numerous new problems have emerged, causing the community activities in the area to be ineffective, such as traffic congestion, vehicle circulation, pedestrian circulation, and waste management. Another issue is the inefficiency of the market building itself. There is a need for improvements in the layout of this building to make it more effective and efficient, as well as to create a structure that attracts people to shop and serves as the main shopping center in Cibarusah District by using the principles of behavioral architecture. The method used to achieve the final design includes field surveys, data collection, data analysis, concept development, and final design. Planning involves rearranging kiosks and stalls within the market by grouping them according to commodities. This is expected to facilitate the control of the building's utilities